The roles and mechanisms of the NF-κB signaling pathway in tendon disorders - Li, Hanyue; Li, Yini; Luo, Shengyu; Zhang, Yan; Feng, Zhenhua; Li, Sen (Frontiers in Veterinary Science, 2024)
Both acute and chronic tendon injuries are the most frequently occurring musculoskeletal diseases in human and veterinary medicine, with a limited repertoire of successful and evidenced-based therapeutic strategies. Inflammation has been suggested as a key driver for the formation of scar and adhesion tissue following tendon acute injury, as well as pathological alternations of degenerative tendinopathy. However, prior efforts to completely block this inflammatory process have yet to be largely successful. Recent investigations have indicated that a more precise targeted approach for modulating inflammation is critical to improve outcomes. The nuclear factor-kappaB (NF-κB) is a typical proinflammatory signal transduction pathway identified as a key factor leading to tendon disorders. Therefore, a comprehensive understanding of the mechanism or regulation of NF-κB in tendon disorders will aid in developing targeted therapeutic strategies for human and veterinary tendon disorders. In this review, we discuss what is currently known about molecular components and structures of basal NF-κB proteins and two activation pathways: the canonical activation pathway and the non-canonical activation pathway. Furthermore, we summarize the underlying mechanisms of the NF-κB signaling pathway in fibrosis and adhesion after acute tendon injury, as well as pathological changes of degenerative tendinopathy in all species and highlight the effect of targeting this signaling pathway in tendon disorders. However, to gain a comprehensive understanding of its mechanisms underlying tendon disorders, further investigations are required.In the future, extensive scientific examinations are warranted to full characterize the NF-κB, the exact mechanisms of action, and translate findings into clinical human and veterinary practice.